Digital Ecology: a medley of computer-centric digital informatics and environmentalism. (22nd September 2010) - Neelakanta, Perambur S.; Sardenberg, Renata C.T.
Digital Ecosystems (DEs) are conceived in 'the image of' complex biological ecology and expressed in terms of unique 'digital environment' ontology. It is populated by 'digital species' that interactively mediate massive information exchange. It is a neoteric terminology of ecosystems mostly applied to the evolution of digital world commensurate with modern information technology (IT) perspectives. Addressed in this paper are concepts of DE with the associated ontology and applications. An example of DE-specific modelling is indicated in terms of evolution/devolution (growth/decay) dynamics of competitive IT-centric business structures specified in dichotomous prey-predator ecology.